Behaviour Analysis of Strengthened-RC Beam with Natural Fiber Reinforced Polymer (NFRP) based on Abaca Fiber by Using Finite Element Method - Taufiq Saidi; Muttaqin Hasan; Zahra Amalia; Muhammad Iqbal (Graduate Program of Syiah Kuala University, 2022)
The use of synthetic Fiber Reinforced Polymer (FRP) as a composite material is an alternative material that has been widely used for strengthening and repairing reinforced concrete structures. However, the high price is one of the obstacles in applying synthetic FRP materials in developing countries such as Indonesia. Utilization of natural fiber as a Natural Fiber Reinforced Polymer (NFRP) composite material is an alternative, especially in shear strengthening of reinforced concrete beams. Because it has good tensile strength and also is environmentally friendly. Technological developments in the field of computing make modelling various aspects easier. One of them is modelling reinforced concrete (RC) beams. ATENA V534 is a software that can be used for finite element-based modelling. Therefore, in this study, the ATENA V534 software was used to evaluate the results of research and testing behaviour of reinforced concrete beams from the previous studies about strengthened beam for shear by using NFRP. Behaviour that is evaluated in the form of load and deflection, the pattern of cracks and failure, and stress and strain of reinforcements. The numerical results obtained in ATENA V534 showed in a good agreement with experimental results.